Numerical study of the boiling heat transfer characteristics of bluff body quenching in cylindrical tube - Moon, Joo Hyun; Lee, Jungho; Lee, Seong Hyuk (Case Studies in Thermal Engineering, 2022)
The present study numerically investigates the characteristics of the forced immersion quenching widely used in material manufacturing processes. The numerical simulation considers the boiling heat transfer occurring at the surface of the hot cylindrical specimen heated at 870 °C during the quenching process with a 20 °C water jet. It also examines the influence of water jet velocity on the forced-immersion quenching process. Once the water flow initially impinges on the top side of the hot steel specimen, a large amount of vapor gets generated but disappears from all sides within a few seconds. The amount of vapor decreases with increased water jet velocity due to the high convective heat transfer, leading to vapor condensation. Moreover, a larger recirculation region appears at the sidewall with high water flow velocity because water vapor formed near the wall escapes. Therefore, the cooling performance of the specimen can primarily be attributed to the boiling and convective heat transfer that occurs within a few seconds. The heat flux and heat transfer coefficient increase with the inlet velocity. Moreover, the cooling rate and uniformity are enhanced owing to the increased boiling and convective heat transfer
Keywords: Boiling heat transfer; Conjugate heat transfer; Convective heat transfer; Heat-transfer characteristics; Immersion quenching; Jets velocities; Quenching process; Volume of fluids; Water flows; Waterjets; Computational fluid dynamics; Conjugate heat transfer; Numerical simulation; Quenching; Volume of fluid